Trust Toward Father dnd Mother: An Indigenous Psychology Analysis On Children's Trust Toward Parents - Diana Elfida; . Hidayat (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2013)
A good parent-child relationship is an important factor for positive behavior development in children as well as protective factor for many problems and disorder. Trust between children and parent will be basic component to build good relationship. The purpose of this research was to explore whether or not children trust their parents and the reason underline trust toward parents. The respondents (205 undergraduate students of UIN Sultan Syarif Kasim Riau) completed two questions asking if you trusts your mother and father, then answer the reason you trusts mother and father. An indigenous psychology approach was used to analys the data. T-test analysis shows there is differences in trusting father and mother. Most of respondents (76,58%) highly trust their mothers, more than toward father (57,07%). The reasons to trust mother are mother's character (38.05%), role (30.24%), relation (22.93%), and reliable (8,78%). On the other hand, children trust father because of father's role (36.59%), relation (29.76%), character (23.41%), and reliable (6.83%). We conclude the main reason to trust mother and father are character and role respectively. This research suggests mothers to show more positive characters and fathers to run the role in child-rearing practices.Keywords: trust, parent-child relationship